2017
DOI: 10.1038/bmt.2016.302
|View full text |Cite
|
Sign up to set email alerts
|

Risk of sinusoidal obstruction syndrome in allogeneic stem cell transplantation after prior gemtuzumab ozogamicin treatment: a retrospective study from the Acute Leukemia Working Party of the EBMT

Abstract: Gemtuzumab ozogamicin (GO) may increase the risk of sinusoidal obstruction syndrome (SOS) when used prior to allogeneic stem cell transplantation (HSCT). We assessed SOS incidence and outcomes after HSCT of 146 adults, with a median age of 50 years, previously receiving GO. SOS prophylaxis was used in 69 patients (heparin n=57, ursodeoxycholic acid n=8, defibrotide n=4). Cumulative incidence (CI) of SOS was 8% (n=11), with death in 3 patients. Median interval between last GO dose and HSCT was 130 days. Overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…In a similar study, Barba et al found that acute hepatic GVHD was found in 17% of patients who underwent allo-HSCT while chronic hepatic GVHD was found in 50% of their cohort [3]. Another multicenter retrospective study by Battipaglia et al that included 146 adults with AML and receiving allo-HSCT, the main cause of liver function abnormalities among patients were acute GVHD (31%), chronic GVHD at 2 years was 25% [10]. Regarding the type of conditioning regimen and hepatotoxicity, we found that busulfan-based conditioning regimens had a statistically significant hepatotoxic effect compared to non-busulfan conditioning regimens.…”
Section: Discussionmentioning
confidence: 91%
“…In a similar study, Barba et al found that acute hepatic GVHD was found in 17% of patients who underwent allo-HSCT while chronic hepatic GVHD was found in 50% of their cohort [3]. Another multicenter retrospective study by Battipaglia et al that included 146 adults with AML and receiving allo-HSCT, the main cause of liver function abnormalities among patients were acute GVHD (31%), chronic GVHD at 2 years was 25% [10]. Regarding the type of conditioning regimen and hepatotoxicity, we found that busulfan-based conditioning regimens had a statistically significant hepatotoxic effect compared to non-busulfan conditioning regimens.…”
Section: Discussionmentioning
confidence: 91%
“…The novel antibody-drug conjugates GO and inotuzumab ozogamicin (INO), calicheamicin conjugates targeted against CD33 and CD22, respectively, were associated with increased risk of VOD/SOS in clinical trials [6,7,17,[50][51][52][53]. Black box warnings regarding the risk of hepatic VOD/SOS with use of each agent are included in their prescribing information documents [54,55].…”
Section: Antibody-drug Conjugates and Vod/sos Riskmentioning
confidence: 99%
“…Patients received GO at 6 mg/m 2 (first induction dose) and 3 mg/m 2 (second induction dose) and could receive up to 8 monthly infusions of 2 mg/m 2 thereafter. The risk of GO-associated VOD/SOS also was assessed retrospectively in 146 adults who received GO treatment for AML before undergoing HSCT [53]. Prophylaxis for VOD/SOS was used in 69 patients (heparin, n = 57; ursodeoxycholic acid, n = 8; defibrotide, n = 4).…”
Section: Antibody-drug Conjugates and Vod/sos Riskmentioning
confidence: 99%
“…As reported in ALFA-0701, the incidence of VOD did not significantly differ between the GO and control arm [6 (4.6%) vs 2 (1.5%), p = 0.165], nor did the result of liver chemistry abnormalities [43]. In another study, out of 146 patients undergoing AlloSCT previously treated with GO, 11 (8%) developed VOD after transplantation, with death in 3 patients, comparable to the incidence of historical cohorts of patients not receiving GO [71]. Prophylaxis of VOD for high-risk patients with agents such as recombinant human soluble thrombomodulin might further lower the risk [72].…”
Section: Safety and Toxicitymentioning
confidence: 91%